Reviews (Zygon, 2004)
Unprecedented Choices: Religious Ethics at the Frontiers of Genetic Science. By Audrey R. Chapman The Mind of the Universe: Understanding Science and Religion. By Mariano Artigas The Philosophy of Nature of St. Thomas Aquinas: Nature, the Universe, Man. By Leo Elders The Far-Future Universe: Eschatology from a Cosmic Perspective. Edited by George F. R. Ellis Rethinking Theology and Science: Six Models for the Current Dialogue. Edited by Niels Henrik Gregersen and J. Wentzel van Huyssteen The Human Person in Science and Theology. Edited by Niels Henrik Gregersen, Willem B. Drees, and Ulf Gorman